Analisis Keputusan Bapepam Atas Kasus Insider Trading PT Bank Mashill Utama Tbk - Ekel, Natalia Grace (LAW REVIEW, 2002)
The development of the economic sector can be known from the growth of the capital market. Capital Market in Indonesia is regulated by the Law of the Republic of Indonesia Number 8/1995 concerning Capital Market. The legal problems in the capital market are mainly related to the violation of the laws concerning capital market, such as misleading information, fraud, market manipulation, insider trading, etc. To avoid the violation, the government must have a policy that laws have to be obeyed by all parties involved. This is important to evoke a good competition in the trading of shares and bonds. There are so many cases related to the insider trading. Insider trading is defined as a trading which is done by an insider who possesses confidential information that has not been disclosed  yet, in order to get the profit. Insider trading will undermine the trust of the investors  and it will inflict a financial loss. Based on those reasons, it is very important to avoid and  solve insider trading by punishing the insiders who manipulate advantages of insider trading.